What have we learned from animal models of idiosyncratic, drug-induced Liver Injury? - Roth, Robert A. (Expert Opin Drug Metab Toxicol, 2020)
INTRODUCTION: Idiosyncratic, drug-induced liver injury (IDILI) continues to plague patients and restrict the use of drugs that are pharmacologically effective. Mechanisms of IDILI are incompletely understood, and a better understanding would reduce speculation and could help to identify safer drug candidates preclinically. Animal models have the potential to enhance knowledge of mechanisms of IDILI. AREAS COVERED: Numerous hypotheses have emerged to explain IDILI pathogenesis, many of which center on the roles of the innate and/or adaptive immune systems. Animal models based on these hypotheses are reviewed in the context of their contributions to understanding of IDILI and their limitations. EXPERT OPINION: Animal models of IDILI based on an activated adaptive immune system have to date failed to reproduce major liver injury that is of most concern clinically. The only models that have so far resulted in pronounced liver injury are based on the multiple determinant hypothesis or the inflammatory stress hypothesis. The liver pathogenesis in IDILI animal models involves various leukocytes and immune mediators such as cytokines. Insights from animal models are changing the way we view IDILI pathogenesis and are leading to better approaches to preclinical prediction of IDILI potential of new drug candidates.